Wisatawan Domestik Kampung Budaya Pasca Pandemi Covid-19 - Rizki Nurul Nugraha; Asep Kurniawan; Dwita Chika Wardani; Firman Riza Dermawan; Sari Meilina Butar-Butar (Jurnal Ilmiah Wahana Pendidikan, 2023)
Cultural village tourism is a cultural village tourism area that still preserves the traditions and culture of its ancestors. Local cultural village tourism that is there is characterized by conditions that are still in harmony with nature. Even though the times and technology are developing rapidly, the people in the area of a cultural village tour still maintain the existing customary traditions. Apart from maintaining existing traditions, the community also introduces domestic tourists to how life is in the area, this includes explaining how the daily life of the tourist population maintains the continuity of ancestral traditions. This paper aims to dig deeper into the prospects for cultural village tourism after the Covid-19 pandemic. In writing this paper, researchers used the literature review research method or literature studies obtained from several sources such as the Unas Journal, Researchgate, and AcademiaEdu. According to the University of Illinois, The Advantages Literature Review allows readers to get to know the latest insights into their particular topic, as well as about its limitations.